2019
DOI: 10.17567/ataunidfd.603744
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Attitudes Toward Periodontal Health Among Parents of Pedodontic Patients

Abstract: Aim:Family is the most important environment where children acquire knowledge, attitudes, and habits related to oral health. The aim of this study was to evaluate the knowledge and attitudes of parents toward periodontal health and diseases, and the relationship of their knowledge and attitudes with demographic data. Materials and Methods: 500 parents, referred for the treatment of their children were included in the study. The knowledge and attitudes of the parents were assessed using a self-administered and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Normally, these individuals are expected to have a higher awareness of toothbrushing. In another study 35 conducted with parents, this rate was reported as 33%, which is consistent with our study.…”
Section: Ta B L Esupporting
confidence: 93%
“…Normally, these individuals are expected to have a higher awareness of toothbrushing. In another study 35 conducted with parents, this rate was reported as 33%, which is consistent with our study.…”
Section: Ta B L Esupporting
confidence: 93%